2018
DOI: 10.1002/jaba.515
|View full text |Cite
|
Sign up to set email alerts
|

Shifting preferences for choice‐making opportunities through histories of differential reinforcer quality

Abstract: Children of both typical and atypical cognitive development tend to prefer contexts in which their behavior results in a choice of reinforcers rather than a single reinforcer, even when the reinforcer accessed is identical across conditions. The origin of this preference has been attributed speculatively to behavioral histories in which choice making tends to be associated with differentially beneficial outcomes. Few studies have evaluated this claim, and those that have, have yielded mixed results. We provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Despite the existence of research on nonfunction-based treatments for problem behavior, research comparing function-based treatments, nonfunction-based treatments, and the combination of function-based and nonfunction-based treatments to reduce problem behavior is limited. In addition, research on participant preference for function-based versus nonfunction-based treatments is also needed; preferred treatments may produce fewer unwanted side effects from participants, which may increase treatment integrity on the part of teachers, caregivers, and others implementing treatments (Drifke, Tiger, & Gifford, 2019). Finally, research on function-based versus nonfunction-based treatments is needed in populations other than individuals with intellectual disabilities.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Despite the existence of research on nonfunction-based treatments for problem behavior, research comparing function-based treatments, nonfunction-based treatments, and the combination of function-based and nonfunction-based treatments to reduce problem behavior is limited. In addition, research on participant preference for function-based versus nonfunction-based treatments is also needed; preferred treatments may produce fewer unwanted side effects from participants, which may increase treatment integrity on the part of teachers, caregivers, and others implementing treatments (Drifke, Tiger, & Gifford, 2019). Finally, research on function-based versus nonfunction-based treatments is needed in populations other than individuals with intellectual disabilities.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Additionally, research has shown that many individuals prefer choice‐making opportunities (Drifke et al., 2019). These findings may shed light on the potential reinforcing qualities of high‐tech items, namely, access to varied stimuli and choice opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, research has shown that many individuals prefer choice-making opportunities (Drifke et al, 2019).…”
Section: Introductionmentioning
confidence: 99%